HUBUNGAN SELF-REGULATED LEARNING DENGAN STUDENT ENGAGEMENT PADA MAHASISWA KARYAWAN FAKULTAS PSIKOLOGI UNIVERSITAS PROKLAMASI 45 YOGYAKARTA - Novia Zahra , Zakiah; Th. Dewi , Setyorini; Femmy, Lekahena (Fakultas Psikologi Universitas Tarumanagara, 2024)
Education influences the quality of employee work. Some employees ultimately choose to attend lectures to train the skills needed by the company. Based on the needs of these employees, the university finally provides employee classes. However, employees who attend lectures will have two demanding roles as employees and students, this will result in role conflicts between the two. The problem with studying while working is that it is not easy to divide your time between studying, working, rest, and other matters. This research aims to determine the relationship between self-regulated learning and student engagement among student employees at the Faculty of Psychology, Proclamation 45 University, Yogyakarta. The hypothesis proposed in this research is that there is a positive relationship between self-regulated learning and student engagement among student employees at the Faculty of Psychology, Proclamation 45 University, Yogyakarta. The sampling technique in this research was to use a probability sampling technique of proportionate random sampling by taking 50% of the population, with a total sample of 112 student employees. The data analysis method used is Karl Pearson's Product Moment correlation and the data collection method uses the self-regulated learning scale and student engagement scale. The results of the research show a relationship between self-regulated learning and student engagement among student employees at the Faculty of Psychology, Proclamation 45 University, Yogyakarta with values of r = 0.818 and p = 0.000, so the hypothesis is accepted. The effective contribution of self-regulated learning to student engagement is 66.91%, the results of additional analysis show that the motivation dimension is 27.43%, the method dimension is 10.65%, the performance results dimension is 15.68% and the social environment dimension is 13.98%.